Measures of and factors influencing teachers' non-task behavior in selected Omani high schools - Al Araimi, Basima Abdul Aziz Ahmed (2013)
The objectives of this study were: to develop and validate two measures of teachers’ nontask behavior (organizational citizenship behavior and deviant work behavior); to describe the extent to which teachers exhibit non- task behavior (organizational citizenship behavior and deviant work behavior) at the high schools in Oman; and to determine the relationships between ethical leadership, ethical climate, job stress, Islamic work ethics and teachers’ nontask behavior (organizational citizenship behavior and deviant work behavior) in the high schools in Oman. To achieve the study objectives; a mixed-method design (sequential exploratory design) was applied and consisted of two phases. In phase one, a qualitative design was conducted. The sample was 9 school principals and 18 teachers in Post-Basic Education Schools (High schools) in Oman. The interview data were analyzed using coding and thematic development procedures. The results of this phase were the identification of three themes for organizational citizenship behavior and the identification of three themes for deviant work behavior, from the perspective and experience of the study participants. The themes were considered as the sub-scales for organizational citizenship behavior and deviant work behavior. In the second phase, a quantitative design was conducted in two stages. The participants for stage one were 217 teachers in Post-Basic Education Schools (High schools). The data were collected using a self-report questionnaire. The obtained data were analyzed using exploratory factor analysis. The results of this stage showed that the organizational citizenship behavior construct produced three factors: organizational citizenship behavior toward students, organizational citizenship behavior toward peers and organizational citizenship behavior toward school with acceptable reliabilities. The exploratory factor analysis results also showed that the deviant work behavior construct produced three factors:deviant work behavior toward students, deviant work behavior toward peers and deviant work behavior toward school with acceptable reliabilities. The sample for stage two were 565 teachers and 198 head teachers in Post-Basic Education Schools (High schools). Stage two begins with the validation of the study constructs (organizational citizenship behavior, deviant work behavior, ethical leadership, ethical climate, job stress and Islamic work ethic). A self-report questionnaire was distributed to teachers (n=565) in high schools to evaluate ethical leadership, ethical climate, job stress and Islamic work ethic. Meanwhile an otherreport questionnaire was distributed to head teachers to evaluate teachers (n=565) who participated in this stage. The data obtained during this stage were analyzed using confirmatory factor analysis and structural equation modeling. Findings for the first objective provided evidence that the developed instruments:organizational citizenship behavior and deviant work behavior achieved sound psychometric properties. The construct validity and reliability of the organizational citizenship behavior and deviant work behavior constructs were tested and found to be acceptable. Findings for the second objective showed that majority of teachers exhibit moderate level of organizational citizenship behavior as a whole. While the results of the level of deviant work behavior, showed that the majority of teachers exhibit low level of deviant work behavior as a whole. Findings for the third objective showed that ethical leadership and job stress have a significant relationship with teachers’ non-task behavior. The results also showed that there was a significant relationship between ethical climate and teachers’ non-task behavior but not in the predicted direction. Further, the results showed that there was no significant relationship between Islamic work ethic and teachers’ non-task behavior. Overall, this study filled the gap in the literature regarding measuring teachers’ non-task behaviors with constructs developed in the Arab (e.g. Oman) and school context. The two developed constructs are useful tools for continuing investigating teachers’ non-task behavior in schools. Further, this study provided another empirical research into existing literature of measuring the level of teachers’ organizational citizenship behavior using otherreport questionnaire and adds new knowledge on the subject of measuring the level of teachers’ deviant work behavior. This information is useful for the policy makers, human resource managers, school principals and teacher supervisors who have to work together to address the issue of teachers ‘non- task behavior in Omani schools through formulating policies and strategies to take account of teachers’ non-task behavior dimensions. Moreover, this study provided another empirical research in the literature regarding investigating factors that influence non- task behavior in the school setting. The findings showed that ethical leadership and job stress influenced teachers’ non-task behavior. The findings are important for the policy makers, human resource managers, school principals and teacher supervisors who have to select, train and provide coaching for the school principal on how to become ethical leaders, and to diagnose the causes of teachers’ job stress in the high schools in Oman, in order to formulate policies and strategies to reduce it. The unexpected findings of ethical climate and Islamic work ethic add new knowledge to the literature, therefore scholars need to conduct further studies to understand why ethical climate may promote unethical behavior such as deviant work behavior and negate ethical behavior such as organizational citizenship behavior. Further research is also needed to investigate why Islamic work ethic may not influence Muslim work behavior and which factors may influence their work behaviors.